2006
DOI: 10.1016/j.ygeno.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The novel centrosomal associated protein CEP55 is present in the spindle midzone and the midbody

Abstract: Centrosomes are the major microtubule nucleating center in the cell; they also contribute to spindle pole organization and play a role in cell cycle progression as well as completing cytokinesis. Here we describe the molecular characterization of a novel human gene, CEP55, located in 10q23.33 that is expressed in multiple tissues and various cancer cell lines. Sequence analysis of the cDNA predicted a protein of 464 amino acids with several putative coiled-coil domains that are responsible for protein-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 32 publications
9
83
0
Order By: Relevance
“…This behavior is well documented for CEP55, which migrates from the centrosome to the midbody upon phosphorylation by Cdk1 and Erk2 (18,33,34). Cell cycle-dependent centrosomal and midbody localization patterns have now also been reported for IST1 (22) and VPS4 (this study) and for the CHMP4-binding protein, TTC19, which was recently show to translocate together with its binding partner, FYVE-CENT, from centrosomes to midbodies (35).…”
Section: Discussionsupporting
confidence: 69%
“…This behavior is well documented for CEP55, which migrates from the centrosome to the midbody upon phosphorylation by Cdk1 and Erk2 (18,33,34). Cell cycle-dependent centrosomal and midbody localization patterns have now also been reported for IST1 (22) and VPS4 (this study) and for the CHMP4-binding protein, TTC19, which was recently show to translocate together with its binding partner, FYVE-CENT, from centrosomes to midbodies (35).…”
Section: Discussionsupporting
confidence: 69%
“…[12][13][14] Consistent with CEP55 being a direct transcriptional target of FOXM1, 7 both CEP55 12 and FOXM1 31 share organ-specific expression in the testis and thymus of normal adult humans. CEP55 is upregulated in hepatocellular carcinoma and its overexpression induces anchorage-independent growth, enhanced cell growth at low serum levels and induction of tumourigenesis in nude mice.…”
Section: Discussionmentioning
confidence: 89%
“…However, it has been shown that the frequency of HNSCCs that have integrated HPV and express high levels E7 is only in the region of 4-16%. 10,11 We have recently shown that aberrant upregulation of FOXM1 serves as a first oncogenic hit by destabilising the genome and subsequent activation of downstream targets which regulates cytokinesis (CEP55, centrosomal protein 55kDa) [12][13][14] and epigenetic/stem-cell factor re-programming (HELLS, helicase lymphoid specific) [15][16][17][18] leading to malignant transformation (anchorage-independent growth) of a premalignant oral keratinocyte line (SVpgC2a). 7 However, the protein expression profiles of CEP55 and HELLS during HNSCC progression have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Cep55 encodes a centrosomal associated protein involved in centrosome duplication, cell-cycle progression, and in the regulation of cytokinesis (41). Kif2c encodes a kinesin-like protein which has a role in bipolar spindle assembly (42).…”
Section: Discussionmentioning
confidence: 99%